Mimbar dan Podium: Kajian atas Masjid Kuno di Nanggroe Aceh Darussalam - Nurman Kholis (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
This article discusses research findings on the availability of the pulpit in the old mosques in the province of Nangroe Aceh Darussasalam (NAD), particularly on the design and position of the pulpit in the mosques. The research shows that the pulpit have been removed and replaced by the lectern in the majority of the mosques. Referring to tradition of the prophet and his companions, the authors emphasizes that the pulpit accomplished by three steps and this lead the conduct of preacher before giving the sermons. In addition, all the speeches uttered on the pulpit have religious meaning and therefore, are sacred.